2013
DOI: 10.1017/s1368980013001341
|View full text |Cite
|
Sign up to set email alerts
|

Review Article Socio-economic determinants of micronutrient intake and status in Europe: a systematic review

Abstract: Objective: To provide the evidence base for targeted nutrition policies to reduce the risk of micronutrient/diet-related diseases among disadvantaged populations in Europe, by focusing on: folate, vitamin B 12 , Fe, Zn and iodine for intake and status; and vitamin C, vitamin D, Ca, Se and Cu for intake. Design: MEDLINE and Embase databases were searched to collect original studies that: (i) were published from 1990 to 2011; (ii) involved .100 subjects; (iii) had assessed dietary intake at the individual level;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
71
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 37 publications
(181 reference statements)
15
71
2
1
Order By: Relevance
“…Our study also showed a strong positive association between income and micronutrient intake. The same positive association is observed between SES and micronutrient intake among children in Western countries (19,21) . Our study suggested that the lower levels of nutrients, protein and micronutrients consumed by children from low-income households compared with higher-income groups were caused by differences in the types of foods consumed, and a lower consumption of fish/shellfish and green vegetables.…”
Section: Nutritional Statussupporting
confidence: 62%
See 1 more Smart Citation
“…Our study also showed a strong positive association between income and micronutrient intake. The same positive association is observed between SES and micronutrient intake among children in Western countries (19,21) . Our study suggested that the lower levels of nutrients, protein and micronutrients consumed by children from low-income households compared with higher-income groups were caused by differences in the types of foods consumed, and a lower consumption of fish/shellfish and green vegetables.…”
Section: Nutritional Statussupporting
confidence: 62%
“…Previous studies using dietary recall/records suggest that children in households with lower incomes consume less Ca, vitamin D and dairy foods in Canada (19) , and a Korean study showed that they obtain less energy from protein and higher energy from carbohydrates (20) . A systematic review revealed a positive association between SES and micronutrient intake in children; however, only a few studies have been published (21) . Very few studies on SES and health/diet have been reported in Japan, because Japanese society is considered an egalitarian society (22) .…”
mentioning
confidence: 99%
“…This research finds that low socio-economic groups are less likely to consume fruits and vegetables, fish, low-fat dairy products and whole grains, and more likely to consume red and processed meat and fast food (5)(6)(7)(8)(9)(10)(11) . Socio-economically disadvantaged adults in high-income countries also have lower intakes of important micronutrients including folate, vitamin C, vitamin D, Ca, Fe, Cu and Se (12) , although there is limited evidence that SEP is associated with total energy or macronutrient intake (7,8) . Studies describing associations between SEP and diet among children, adolescents and the elderly in high-income countries also show that individuals from disadvantaged backgrounds are more likely to have food and micronutrient intakes that are least consistent with dietary guidelines or reference intakes (12,13) .…”
Section: Current Evidence On Socio-economic Inequalities In Diet and mentioning
confidence: 99%
“…The identification of potential predictive factors may allow better prevention and management of malnutrition in elderly people (Boulos et al, 2014). Socio-economic determinants of micronutrient intake and status in Europe have been reported that there is a positive association between indicators of socio-economic status and micronutrient intake and/or status (Novaković et al 2014). Meanwhile, the elderly behavior regarding to food consumed that were related to liver fluke infection was found that the majority of them had a high knowledge, moderately attitude, and moderately practice, however, many of them is found the risk factor to liver fluke infection in this group.…”
Section: Discussionmentioning
confidence: 99%